Association of Major Adverse Cardiac Events up to 5 Years in Patients With Chest Pain Without Significant Coronary Artery Disease in the Korean Population. Issue 12 (18th June 2019) - Choi, Byoung Geol; Rha, Seung‐Woon; Yoon, Seong Gyu; Choi, Cheol Ung; Lee, Min Woo; Kim, Suhng Wook
Abstract : Background: Significant coronary artery disease has a well‐known association with long‐term adverse cardiovascular events. In this study, we aimed to evaluate its association with long‐term major adverse clinical events (MACE) up to 5 years in patients who presented with chest pain without significant coronary artery disease. Methods and Results: A total of 5890 subjects with chest pain without significant coronary artery disease were prospectively enrolled in this study. The mean follow‐up duration was 3.4 years. Multivariable Cox proportional hazards regression analysis was performed for assessing the independent risk factors for MACE or sustained angina pectoris. MACE was defined as the composite of total death, myocardial infarction, coronary revascularization, stroke, and hospitalization because of heart failure. Ninety‐one (2.2%) patients developed MACE, and 309 (8.1%) patients developed sustained angina pectoris, both within 5 years. In multivariable Cox proportional hazards regression analysis, the risk of MACE was significantly associated with age (per 5 years; hazard ratio [HR], 1.44; 95% CI, 1.30–1.60) and insignificant coronary stenosis (30%–70%; HR, 2.03; 95% CI; 1.28–3.21). The risk of sustained angina pectoris was significantly associated with age (per 5 years; HR, 1.05; 95% CI, 1.01–1.11), dyslipidemia (HR, 1.34; 95% CI, 1.06–1.70), insignificant coronary stenosis (HR, 2.54; 95% CI, 1.94–3.31), coronary artery spasm (HR, 1.42; 95% CI, 1.11–1.80), and myocardial bridge (HR, 1.37; 95% CI, 1.04–1.81). Conclusions: In patients without significant CAD, aging and insignificant coronary stenosis have a strong association with future long‐term MACE. Also, aging, dyslipidemia, insignificant coronary stenosis, coronary artery spasm, and myocardial bridge are strongly associated with future angina pectoris.